A Crítica de Immanuel Kant à psicologia racional - Barbosa, João de Jesus (2018)
The current work aims to understanding Kant's critique of the so-called speculative or rational psychology, one of the three branches of the special metaphysics of his time. Due to the results of his critique of knowledge, Kant considers rational psychology as based on false reasoning, which he calls paralogisms. These errors are not casual, but the result of an inherent necessity in the nature of reason, which leads to such mistakes. Kant realizes the critique of these inevitable illusions, through conceptual innovations that allow him to reinterpret the conclusions of rational psychology. In the first chapter, we will drawn the general plan of transcendental philosophy, the meaning of "rational psychology", the problematic of this field of study, and the place of criticism of rational psychology in Kantian philosophy. In the second, we will explain how the peculiar development of the concept of "I" throughout the Critique of Pure Reason allowed Kant to develop the conceptual tools necessary for critical realization. In the third, we will discuss some problems related to the success of this critique in the scope of critical philosophy. I conclude by pointing to the simultaneous presence of strong continuities and discontinuities in Kant's conclusions in relation to the rationalistic model of attacking thought